2014
DOI: 10.1051/matecconf/20141101024
|View full text |Cite
|
Sign up to set email alerts
|

Buckling of Functionally Graded Nanobeams Based on the Nonlocal New First-Order Shear Deformation Beam Theory

Abstract: Abstract. In this work, the size-dependent buckling behavior of functionally graded (FG) nanobeams is investigated on the basis of the nonlocal continuum model. The material properties of FG nanobeams are assumed to vary through the thickness according to the power law. In addition, Poisson's ratio is assumed constant in the current model. The nanobeams is modelled according to the new first order shear beam theory with small deformation and the equilibrium equations are derived using the Hamilton's principle.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2018
2018
2019
2019

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 10 publications
0
1
0
Order By: Relevance
“…where 0 u , 0 v , and 0 w are three unknown displacement functions of midplane of the plate and β is a parameter of the present displacement model. ) (z f is a shape function representing the distribution of the transverse shear strains and shear stresses through the thickness of the plate and is given as [65]:…”
Section: Kinematics Of the Present Plate Modelmentioning
confidence: 99%
“…where 0 u , 0 v , and 0 w are three unknown displacement functions of midplane of the plate and β is a parameter of the present displacement model. ) (z f is a shape function representing the distribution of the transverse shear strains and shear stresses through the thickness of the plate and is given as [65]:…”
Section: Kinematics Of the Present Plate Modelmentioning
confidence: 99%
“…Rychlewska (2014) presented the critical buckling loads for axially functionally graded (FG) beams subjected to a distributed axial load and found that the critical buckling loads of a homogeneous beam calculated by the proposed approach were in good agreement with those available in literature. Houari et al (2013) investigated the size-dependent buckling behaviour of functionally graded (FG) nanobeams on the basis of the nonlocal continuum model. The effects of the nonlocal parameter, aspect ratio, various material compositions on the stability responses of the FG nanobeams were discussed.…”
Section: Introductionmentioning
confidence: 99%